Hazard Perception and Demand for Insurance among Selected Motorcyclists in Lagos, Nigeria - Ismaila, Adeleke; Feyisayo, Olowokudejo Folake; Ajemunigbohun, Sunday Stephen (UI Scholars Hub, 2016)
This study examines hazard perception effects on the demand for insurance with special focus on motorcycle riders in Lagos state. For this purpose, the researchers have been able to examine selected hazard perception determinants and their effects on the insuring attitude and desire of motorcycle riders. An explanatory research design was employed and a convenience sampling type of the nonprobability sampling technique was adopted. Data was gathered by interviews conducted at motorcycle parks along the Lagos-Badagry expressway. The sample consisted of 126 respondents made up of commercial motorcycle riders within the sample areas. Data collected was analysed using multiple regression technique. The study was able to establish some level of contributory linkage between hazard perception and demand for motorcycle insurance. The findings show that while dread and trust both appeared to have significant effect, publicity and controllability both have positive contributory effect; furthermore, choice expressed an inverse relationship with demand for insurance among the motorcycle riders. The study therefore recommends pre-loss and post-loss measures among the motorcycle riders so that unforeseen motorcycle risks can be managed. Also, insurance companies should endeavour to invest more on enlightening the motorcycle riders in order to lessen their dread of loss outcome, and thus, design policy that can instil trust in motorcycle riders in insurance as a loss control measure.